438 THE IMPACT OF ROUTE OF RECONSTRUCTION FOLLOWING THREE PHASE ESOPHAGECTOMY: AN UPDATED PERSPECTIVE. (14th September 2020) - Wong, C; Luk, Y; Chan, D; Wong, I; Chan, F; Law, B; Law, S
Abstract: : The retrosternal space (RS) and posterior mediastinum (PM) are the two common routes for reconstruction after three-phase esophagectomy. It remains controversial if the choice of route impacts on post-operative outcome. This study aims to compare the two routes in the era of increased application of multimodal therapy. Methods: In a single tertiary center, patients who had squamous cell carcinoma of the esophagus and underwent three-phase esophagectomy with gastric conduit reconstruction via either the RS or PM routes between 2002 and 2017 were studied. Patient demographics, surgical outcomes and survival were analyzed from a prospectively managed database. Results: 345 patients were included (271 men); RS 73 and PM group 272. Demographics were not different. Between RS and PM, proportion of neoadjuvant therapy (59%vs.63%, p = 0.536) and thoracoscopic resection (61.6% vs.72%, p = 0.116) were comparable. More advanced disease was found in RS, with fewer R0 resections (36.9% vs.90%, p < 0.001) and more advanced pT&pN stages (p = 0.000&0.008). Operative results were presented in Table 1. In the RS group, there was more blood loss (p = 0.015) and anastomotic leaks (p = 0.03). Cardiopulmonary complications, 30-and 90-day mortality were comparable. On multivariate analysis for 90-day mortality R-category was the only independent factor (p = 0.014). Overall survival was worse for RS (p = 0.000), but not different when only R0 resections were selected. Conclusion: The RS route was more often the choice for reconstruction in loco-regionally advanced disease. Compared with PM route, more anastomotic leaks were found. Survival was not different between RS and PM routes when resection was curative.